The prognostic value of the Koret CT score in dogs following traumatic brain injury. (December 2020) - Rapoport, K.; Mateo, I.; Peery, D.; Mazaki-Tovi, M.; Klainbart, S.; Kelmer, E.; Ruggeri, M.; Shamir, M.H.; Chai, O.
Highlights: Prognostication of dogs with traumatic brain injury (TBI) is highly challenging. Koret CT score (KCTS) is a newly published computed tomography (CT)-based scoring index for dogs with TBI. KCTS was significantly associated with short- and long-term survival of TBI dogs. A cutoff of 3 points predicted survival with 85% sensitivity and 100% specificity. Using KCTS may improve outcome prediction accuracy in dogs with TBI. Abstract: Traumatic brain injury (TBI) is a common condition in veterinary medicine with relatively high mortality rate. Recently, a study that correlated abnormal computed tomography (CT) findings with outcome in dogs with head trauma established a prognostic scoring system termed Koret CT score (KCTS). The purpose of this study was to evaluate the accuracy of the KCTS in making short- and long-term prognosis in dogs presented within 72 h of TBI. Thirty-five dogs that were admitted to a hospital during 2010–2019 with TBI and were CT-scanned within 72 h of injury were included in the study. Retrospectively collected data included signalment, modified Glasgow Coma Scale score (MGCS), CT findings, and outcome, i.e. short-term (defined as 10 days) and long-term (6 months) survival. CT images were reviewed and the KCTS was calculated for all dogs. Association between KCTS and outcome was examined. A significant negative association was found between KCTS and both short- and long-term survival. The area under receiver operating characteristic curve for KCTS for short- and long-term survival was 0.9 and 0.87, respectively. Furthermore, the probability of survival in the short term was predicated by the KCTS in an almost linear fashion and a score of 3 points or less on the KCTS was associated with survival with 85% sensitivity and 100% specificity. These results validate the prognostic value of the KCTS in dogs with TBI and provide a complementary tool for serial clinical and neurological evaluation.